Sécurité alimentaire de l’agriculture indigène guatémaltèque face à l’incertitude sociale et climatique - Julien Malard-Adam; Jan Adamowski; Héctor Tuy; Hugo Melgar-Quiñonez (VertigO)
Given the increasing pressures exerted by climate change on small-scale agriculture, the importance of participatory modelling methodologies that can consider both the human and environmental components of these systems has become more and more evident. The current study presents a socioeconomic system dynamics model of the food and environmental systems of the predominantly Indigenous region of Tz’olöj Ya’, Guatemala. The model was built in a participatory manner with stakeholders from the region and was then coupled to an external crop growth model before being applied to the analysis of the impact of future climate change and its potential interactions with various stakeholder-proposed policies. The analysis identified several feedback loops between environmental and human components of the system that can lead to counterintuitive responses to the proposed policies. At the same time, the use of an external crop growth model allowed for a more realistic, yet still easily implementable, representation of the impacts of climate change on crop production. This analysis is the first to use a socioeconomic system dynamics model coupled with an external crop growth model to analyse food security in the context of a local socio-environmental food system.